Early pathological changes in the liver and kidney of non-obese diabetic (NOD) mice: involvement of iron accumulation and ferroptosis - Stancic, Ana; Markelic, Milica; Savic, Nevena; Velickovic, Ksenija; Martinovic, Vesna; Gudelj, Andjelija; Velickovic, Danica; Grigorov, Ilijana; Otasevic, Vesna (Frontiers in Endocrinology, 2025)
Disorders of iron metabolism and ferroptosis play an important role in the development of diabetes and related pathologies. The involvement of ferroptosis in type 1 diabetes has mainly been investigated in animal models with chemically induced diabetes. Our aim was to examine the involvement of iron homeostasis disturbances and ferroptotic events in liver and kidney damage in non-obese diabetic (NOD) mice in the early phase of spontaneous development of diabetes (15 days of stable hyperglycemia). We found an accumulation of iron and lipid peroxides in the proximal tubule epithelial cells (PTECs) of the renal cortex and in the liver. This was accompanied by a decrease in the level of proteins involved in the sequestration (ferritin) and export (ferroportin) of iron and an increase in the level of transferrin receptor 1 in both organs. The level of activated nuclear factor erythroid 2-related factor 2 was decreased in both liver and kidney, whereas lower levels of Xc- glutamate/L-cystine antiporter and glutathione peroxidase 4 were detected only in PTECs, demonstrating the proferroptotic events in these cells. In conclusion, although iron accumulation and lipid peroxidation occur in both organs, the kidneys are more susceptible to ferroptosis in early diabetes development.